Efeito da adição de probiótico e/ou prebiótico em dietas de leitões desmamados sobre o desempenho, incidência de diarréia e contagem de coliformes totais - Budiño, Fábio Enrique Lemos [UNESP]; Thomaz, Maria Cristina [UNESP]; Kronka, Rodolfo Nascimento [UNESP]; Tucci, Fernanda Marcussi [UNESP]; Fraga, Alessandro Luís [UNESP]; Scandolera, Antônio João [UNESP]; Huaynate, Rizal Alcides Robles [UNESP]; Nadai, Arnaldo [UNESP]; Correia, Rodrigo César [UNESP] (My University, 2006)
In the Experiment 1, 50 pigs weaned at the 21 days were fed with either of five diets: T1 - basal diet; T2 - basal diet + antibiotic; T3 - basal diet + probiotic; T4 - basal diet + prebiotic; T5 - basal diet + simbiotic. The variables studied were body weight, feed intake and feed conversion in the Phase 1 (21 to 43 days), Phase 2 (44 to 57 days), Phase 3 (58 to 70 days) and Total Phase (21 to 70 days). During the performance experiment, a fecal survey score was conducted to verify diarrhea incidence. In the Experiment 2, 44 pigs weaned at 21 days were fed with the same diets of Experiment 1. Pigs were slaughtered at three differents ages (at weaning, at seven and 14 days after weaning). A segment of the small intestine was collected for analisys of total coliformes. The results showed that the best performance was obtained with the utilization of prebiotic and simbiotic. There were not differences in relation to diarrhea incidence among the treatments studied. The addition of probiotic and/or prebiotic in the diet prevented increase of colonization by pathogenic bacterias from seven to 14 days after weaning.
Effect of dietary addition of probiotic and/ or prebiotic on performance, diarrhea incidence and total coliforms count of weaned pigs
Keywords: Antibiotic; Frutooligosaccharide; Simbiotic; Swine; Suidae